Morpho-quantitative assessment and biochemical characterization of grain amaranth (Amaranthus hypochondriacus) to determine the nutritional composition - SAHOO, A R; BEHERA, L; SAHOO, J P; SAMAL, K C; MISHRA, D; NAGALLA, S Y; PRAVEENA, J; NARGAVE, C S (The Indian Journal of Agricultural Sciences, 2024)
Grain amaranth (Amaranthus hypochondriacus L.) has gained increasing attention as a potential nutrient-rich crop with numerous health benefits. The present study was carried out, during the summer (kharif) season of 2019 and 2020 at College of Agriculture, Odisha University of Agriculture and Technology, Bhubaneswar, Odisha to evaluate morpho-quantitative and biochemical parameters of grain amaranth. Four varieties of grain amaranth in five different replications were taken. Morpho-quantitative assessment indicated that, Suvarna (11.23 q/ha) yielded the most, GA 2 flowers opened 50% after 45.68 days, whereas BGA 2 took 51.52 days. The RMA 7 variety matured in 102.5 days, while the Suvarna variety matured in 104.2 days. RMA 7 had the longest panicle (38.9 cm), whereas Suvarna had the smallest (35.68 cm). Suvarna had the most plants (74.3), followed by BGA 2 (73.5). Biochemical analysis revealed that, BGA 2 contained more chlorophyll (1.537 mg/g), and RMA 7 had more total carbohydrate (319 mg/g). Moreover, BGA 2, GA 2, Suvarna and RMA 7 exhibited comparable phenol content. Moreover, Fe (66 mg/100 g), Mg (284.5 mg/100 g), Mn (5.71 mg/100 g), Zn (11.3 mg/100 g), Ca (178.7 mg/100 g), and K (400.50 mg/100 g) were detected by ICP-OES analysis. FTIR and HPTLC analysis indicated more number of functional group present in the varieties. Thus, the present study unveiled that seeds of grain amaranthus varieties are rich source of different essential elements, and other essential biochemical parameters, with higher antioxidant activity. Hence this pseudocereal can be used to provide good food supplements to the infants as well as adults.